Every 8-Traceable Oriented Graph Is Traceable - Aardt Susan A. van (Discussiones Mathematicae Graph Theory, 2017)
A digraph of order n is k-traceable if n ≥ k and each of its induced subdigraphs of order k is traceable. It is known that if 2 ≤ k ≤ 6, every k-traceable oriented graph is traceable but for k = 7 and for each k ≥ 9, there exist k-traceable oriented graphs that are nontraceable. We show that every 8-traceable oriented graph is traceable.